Voltammetric and viscometric studies of flavonoids interactions with DNA at physiological conditions - Hussain, Syed Tajammul; Siddiqa, Asima (European Journal of Chemistry, 2011)
Cyclic voltammetric behaviour of three flavonoids: quercetin, morin and rutin was investigated for their interaction with DNA at pH = 4.7 and pH = 7.4 at body temperature (310 K), using glassy carbon electrode. The diffusion coefficients of the free and DNA bound forms of the flavonoids were evaluated using Randles–Sevcik equation. The binding parameters like binding constant, binding site size and binding free energy were also determined from voltammetric data. Moreover, the binding modes of flavonoids with DNA were evaluated from viscommetric analysis. A comparatively high value of binding constant, binding site size and diffusion coefficients for quercetin reveals its stronger binding with DNA under physiological conditions. The negative values of ∆G indicate the spontaneity of binding of flavonoids with DNA.